Decoupling the downstream effects of germline nuclear RNAi reveals that H3K9me3 is dispensable for heritable RNAi and the maintenance of endogenous siRNA-mediated transcriptional silencing in Caenorhabditis elegans. Issue 1 (December 2017) - Kalinava, Natallia; Ni, Julie; Peterman, Kimberly; Chen, Esteban; Gu, Sam
Abstract Background Germline nuclear RNAi inC. elegans is a transgenerational gene-silencing pathway that leads to H3K9 trimethylation (H3K9me3) and transcriptional silencing at the target genes. H3K9me3 induced by either exogenous double-stranded RNA (dsRNA) or endogenous siRNA (endo-siRNA) is highly specific to the target loci and transgenerationally heritable. Despite these features, the role of H3K9me3 in siRNA-mediated transcriptional silencing and inheritance of the silencing state at native target genes is unclear. In this study, we took combined genetic and whole-genome approaches to address this question. Results Here we demonstrate that siRNA-mediated H3K9me3 requires combined activities of three H3K9 histone methyltransferases: MET-2, SET-25, and SET-32.set -32 single, met -2 set -25 double, andmet -2 set -25;set -32 triple mutant adult animals all exhibit prominent reductions in H3K9me3 throughout the genome, withmet -2 set -25;set -32 mutant worms losing all detectable H3K9me3 signals. Surprisingly, loss of high-magnitude H3K9me3 at the native nuclear RNAi targets has no effect on the transcriptional silencing state. In addition, the exogenous dsRNA-induced transcriptional silencing and heritable RNAi atoma -1, a well-established nuclear RNAi reporter gene, are completely resistant to the loss of H3K9me3. Conclusions Nuclear RNAi-mediated H3K9me3 inC. elegans requires multiple histone methyltransferases, including MET-2, SET-25, and SET-32. H3K9me3 is not essential for dsRNA-induced heritable RNAi or the maintenance of endo-siRNA-mediated transcriptional silencing inC. elegans . We propose that siRNA-mediated transcriptional silencing inC. elegans can be maintained by an H3K9me3-independent mechanism.